2022
DOI: 10.3390/ma15093162
|View full text |Cite
|
Sign up to set email alerts
|

Response of Various Yb3+-Doped Oxide Glasses to Different Radiation Treatments

Abstract: The radiation effects of electrons and protons on the spectroscopic and optical properties of oxide glasses doped with Yb3+ in various glass systems were investigated to understand the impact of the glass composition on the glass photo-response. Changes in the optical and emission properties were seen after the radiation treatment, and the magnitude of the changes depended on the irradiation source and dose. For all the investigated materials, the absorption coefficients in the 200–550 nm range increase post-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…Density of the glasses increases with the concentration of Yb 2 O 3 , in agreement with previously reported data 18 . Similarly the refractive index increases due to the adding of heavy lanthanide ions as compared to the much lighter ions in the base glass.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Density of the glasses increases with the concentration of Yb 2 O 3 , in agreement with previously reported data 18 . Similarly the refractive index increases due to the adding of heavy lanthanide ions as compared to the much lighter ions in the base glass.…”
Section: Resultssupporting
confidence: 91%
“…Figure 3B displays the Yb 3+ absorption coefficient for the characteristic 2 F 5/2 – 2 F 7/2 transition of the Yb 3+ ion. The shape and intensity of the absorption are consistent with previous report on borosilicate glasses doped with Yb 3+ 18 . As can be seen in Figure 3C,D, the emission intensity increases up to 1.0% Yb 2 O 3 before it decreases for 1.25% due to concentration quenching.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The above vibrational spectroscopies were successfully applied to examine the local structure of borate [ 4 , 5 ], phosphate [ 6 , 7 ], tellurite [ 8 , 9 ], silicate [ 10 , 11 ], and germanate [ 12 , 13 , 14 , 15 , 16 ] glass-host matrices. Studies in the last decade have shown that basic glass composition can be realized by adding several oxides and/or fluoride additives [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%